A safety review of proton pump inhibitors to treat acid-related digestive diseases. Issue 8 (3rd August 2018) - Savarino, Edoardo; Marabotto, Elisa; Zentilin, Patrizia; Furnari, Manuele; Bodini, Giorgia; Pellegatta, Gaia; Lorenzon, Greta; Della Coletta, Marco; Ghisa, Matteo; Coppo, Claudia; Marinelli, Carla; Savarino, Vincenzo
ABSTRACT: Introduction: Proton pump inhibitors (PPIs) have become the first choice medical treatment of acid-related disease and, as with any pharmacological agent, they have been reported to be associated with some adverse events mainly linked to their chronic use. The most important postulated harms are represented by serum electrolyte alterations, vitamin B12 and iron deficiency, gastric tumors, enteric infections, spontaneous bacterial peritonitis, pneumonia, ischemic heart attacks, bone fractures, chronic kidney disease, dementia, and Alzheimer disease. Specific pathophysiological mechanisms have been identified for some of them and not for other manifestations. Areas covered: However, studies on PPIs safety have generally important limitations because of their frequent retrospective design and other methodological drawbacks, such as patients' selection and residual confounders. Expert opinion: Obviously, in the vast majority of the cases, adverse drug reactions cannot be assessed by means of randomized clinical trials due to the high costs, ethical reasons, and difficulties in performing prospective observational studies. So far, assessment of retrospective observational investigations remains the only method to evaluate adverse events with any drug in general and, although the weaknesses of these studies are evident, the awareness of the reported associations with the medications analyzed is important for physicians in order to manage adequately their individual patients.